(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In the article at the forefront stands creative attitude towards the tradition of prominent Azerbaijani poet Aliaga Kurchayli. Author follows creative work of the poet’s tradition in the folk, classical and contemporary world literature according to the facts and tries to show in which way the poetry formation is reveled. Folklore traditions in A.Kurchayli’s poetry need to be looked for, first of all, in a basis, in soul of its works. Being the son of the people of A.Kurchayli looks at these moral problems from a prism of intelligence, reflections of the Azerbaijani people and estimates them by these criteria. In its works there are a lot of aphorisms, conformable with national legends.